Implicit consumer preferences and their influence on product choice - Friese, Malte; Wänke, Michaela; Plessner, Henning (Psychology & marketing, 2006)
Recent theories in social psychology assume that people may have two different attitudes toward an object at the same time—one that is explicit and corresponds with deliberative behavior, and one that is implicit and corresponds with spontaneous behavior. The research presented in this article tested this assumption in the consumer domain with an experimental approach. Participants whose explicit and implicit preferences regarding generic food products and well-known food brands were incongruent were more likely to choose the implicitly preferred brand over the explicitly preferred one when choices were made under time pressure. The opposite was the case when they had ample time to make their choice. On the basis of these results, the discussion stresses the importance of impulsive behavior and implicit measures for research in the area of consumer behavior. © 2006 Wiley Periodicals, Inc.